Examination of udder morphology in a Hungarian Jersey herd - Orbán, Martina; Németh, Szabina; Tóth, Tamás; Gulyás, László (Animal welfare, Ethology and Housing Systems (AWETH), 2009)
The authors held an udder morphology inquiry in a domestic first lactational Jersey pedigree cow flock (n = 268). Author’s aim was after collecting the udder’s morphologian characters together to find relation between the udder’s different parameters, such as udder depth, distances of the two forwards, two backwards, forward-backwards teats, length and diameter of the teats, as well as the milk’s somatic cell number. The udder area bordered by teats (cm2) and the teats’ volume (cm2) were calculated with using the formulas created by the authors. The examinated cow flock showed in cases of udder depth 37.2–39.0 cm, of the distance of the two forward teats 15.24–16.70 cm, in case of the backward teats the same distance was 8.16–10.43 cm, of the forward and the backward teats 12.60–14.17 cm, of the length of teat 5.03–5.43 cm and of the teat’s diamater 18.12–18.8 cm rates. The average somatic cellnumber was 238 tousand/ml. Statistically proved (P < 0.05) negative coherence was observed on the flock level as well as in case of troops of bull descendants between the somatic cellnumber and the udder depth (r = -0.12), - the distance of the two forward teats (r = -0.22), - the distance of the two backward teats (r = -0.26), the distance of the forward and the backward teats (r = -0.25) and between the diameter of udder teats (r = -0.21). The results of the inquiries call attention to the fact, that the somatic cellnumber’s fluctuation can be determinated beside by many other influential facts (eg. feeding, milking and farming technology, management) also by the udder morfology.
Keywords: jersey; udder morphology; teat’s distance; teat’s length; teat’s diameter; somatic cellnumber